THE CASE OF HEAVY COURS OF OPISTHORCHIASIS - N. I. Tumolskaya (Сеченовский вестник, 2012)
The present study reports one case 43-year-old male patient, living in an opistorchiasis endemic area. The patient had splenectomia after traumatic rupture of spleen 32 years ago. The clinical symptoms were fever, hepatomegaly, hyperleucocytosis, hypereosinophilia. The serological tests with parasitic and infectious diseases were negative. Abdominal ultrasound and CT revealed 2–3 cm focuses in hepatic parenchyma, diagnosed as metastatics. Diagnostic laparotomy, biopsy and morphology investigation revealed cholangiohepatitis, eosinophilia and step by step necrosis of hepatic parenchyma. The diagnosis of opistorchiasis was established 2 month later by serological test with antigen O. felineus. Clinical diagnosis was superinvasive opistorchiasis. The recovery after treatment with biltricide. The causes of peculiarity and seriously cours of disease and difficulty of diagnosis was discussed.